2017
DOI: 10.1371/journal.pone.0173144
|View full text |Cite|
|
Sign up to set email alerts
|

Hyperleptinemia in children with autosomal recessive spinal muscular atrophy type I-III

Abstract: BackgroundAutosomal-recessive proximal spinal muscular atrophies (SMA) are disorders characterized by a ubiquitous deficiency of the survival of motor neuron protein that leads to a multisystemic disorder, which mostly affects alpha motor neurons. Disease progression is clinically associated with failure to thrive or weight loss, mainly caused by chewing and swallowing difficulties. Although pancreatic involvement has been described in animal models, systematic endocrinological evaluation of the energy metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 42 publications
(44 reference statements)
0
23
0
Order By: Relevance
“…As reported in the part on nutritional care, occasional cases of pancreatic dysfunction including diabetes and alterations in glucose metabolism have been reported in SMA patients [56]. Hyperleptinemia has been identified in SMA patients with types 1, 2 and 3 [57]. Mitochondrial dysfunction has been described in patients and human neuronal cell lines [21,58,59].…”
Section: Other Organ System Involvementmentioning
confidence: 87%
“…As reported in the part on nutritional care, occasional cases of pancreatic dysfunction including diabetes and alterations in glucose metabolism have been reported in SMA patients [56]. Hyperleptinemia has been identified in SMA patients with types 1, 2 and 3 [57]. Mitochondrial dysfunction has been described in patients and human neuronal cell lines [21,58,59].…”
Section: Other Organ System Involvementmentioning
confidence: 87%
“…The high variability in metabolic alterations in SMA patients (Dahl and Peters, 1975; Bruce et al, 1995; Tein et al, 1995; Crawford et al, 1999; Berger et al, 2003; Sproule et al, 2009; Zolkipli et al, 2012; Davis et al, 2015; Bertoli et al, 2017; Kolbel et al, 2017) and mouse models (Bowerman et al, 2012, 2014; Ripolone et al, 2015) can preclude or limit the application, design or efficiency of therapies, including active exercise. Thus, deciphering the origin and mechanisms involved in those metabolic alterations and the way to modulate them appeared crucial.…”
Section: Discussionmentioning
confidence: 99%
“…It is admitted today that the metabolic status of SMA patients are diverse, notably in terms of diabetes, obesity or insulinemia (Davis et al, 2015; Kolbel et al, 2017), resulting in different abilities for them to perform active exercise. Therefore, particular attention should be paid to the exercise paradigm used, in order to fit the training protocol to the expected metabolic adaptation of each patient.…”
Section: Discussionmentioning
confidence: 99%
“…While it remains unclear whether intrinsic metabolic defects in specific cells and tissues such as motoneurons, skeletal muscle, glial cells and lymphoid organs or a systemic metabolic dysregulation are the source of dyshomeostasis in SMA and ALS, patients nevertheless present syndromes that have well-documented severe functional consequences. Indeed, instances of hyperinsulinemia (Bowerman et al, 2014;Davis et al, 2015), insulin resistance (Davis et al, 2015;Reyes et al, 1984), hyperlipidemia (Dahl and Peters, 1975;Dedic et al, 2012), hyperglycemia (Melissa Bowerman et al, 2012;Shimizu et al, 2011), hyperleptinemia (Kölbel et al, 2017), aberrant fatty acid metabolism (Pradat et al, 2010;Zolkipli et al, 2012), hypoglycemia (Bruce et al, 1995), hyperglucagonemia (Melissa Bowerman et al, 2012;Hubbard et al, 1992), glucose intolerance (Davis et al, 2015;Pradat et al, 2010) and development of diabetes (Borkowska et al, 2015;Hamasaki et al, 2015) have all been reported in SMA and ALS patients and animal models. As we move along therapeutic progress for both diseases, it will be interesting to see if the gene-targeted therapies correct the metabolic abnormalities described herein or if they will have to be complemented with interventions aimed at restoring metabolic homeostasis.…”
Section: Please Place Figure Herementioning
confidence: 99%